Comparison of the forms of carbohydrate metabolism in children with cystic fibrosis: A review - Nadezhda V. Liabina; Pavel A. Tikhonovskiy; Olga I. Simonova; Serafima G. Bystrova; Ina Sokolov; Irina V. Shirokova (ZAO "Consilium Medicum", 2024)
Background. Forms of glucose metabolism disorders are one of the key processes in the course of cystic fibrosis (CF) and can be variable, starting with impaired glucose tolerance (IGT) and ending with cystic fibrosis-related diabetes (CFRD), which is the most dangerous complication, worsening the prognosis and outcome of disease. Decreased lung function and poor nutritional status are the leading causes of morbidity and mortality in patients with carbohydrate metabolism disorders (CMD). Materials and methods. The study included 85 children with CF. Patients underwent measurement of anthropometric parameters (height, weight) to assess nutritional status (NS), and spirometry test was used to assess pulmonary function (PF). Of these, 78 patients were assessed with an oral glucose tolerance test (OGTT) at 5 points (0 minutes, 30 minutes, 60 minutes, 90 minutes, 120 minutes) assessing the concentration of venous plasma glucose in mmol/l. The results of the OGTT were assessed in accordance with the diagnostic criteria for CFRD. Results. According to the Kruskal-Wallis test, the maximum volumetric flow rate during exhalation of 75% FVC (FEF 75) differed between different forms of carbohydrate metabolism (p=0.031). Other indicators of respiratory function didn't have any significant differences. Using the Mann-Whitney test, pairwise comparisons were performed, so the FEF 75 indicator was statistically significantly lower in the group of children with CFRD than in other groups. There were no statistically significant differences when assessing Z-scores weight/age (WAZ) and height/age (HAZ) depending on the forms of carbohydrate metabolism. However, BMI/age Z-scores (BAZ) were statistically significantly lower in groups of children with CFRD than in other forms of carbohydrate metabolism. Conclusion. Children with CF in the period of prediabetes don't have significant impairments in lung function and NS. These disorders are typical for children with CFRD.